2005
DOI: 10.1128/mcb.25.23.10286-10300.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroplasticity-Associated Arc Gene Is a Direct Transcriptional Target of Early Growth Response (Egr) Transcription Factors

Abstract: Early growth response (Egr) transcription factors (Egr1 to Egr4) are synaptic activity-inducible immediate early genes (IEGs) that regulate some aspects of synaptic plasticity-related to learning and memory, yet the target genes regulated by them are unknown. In particular, Egr1 is essential for persistence of late-phase long-term potentiation (L-LTP), for hippocampus-dependent long-term memory formation, and for reconsolidation of previously established memories. Here, we show that Egr1 and Egr3 directly regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
182
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(194 citation statements)
references
References 42 publications
11
182
0
1
Order By: Relevance
“…Our own data suggested that a proximal region possessed a 2-to 3-fold transcriptional activation ability, consistent with a previous study that showed the contribution of cAMP/MAPK pathways in the activity-dependent response mediated by this region (23). Furthermore, Egr-1/3 may also mediate the late, protein-synthesis dependent phase of Arc/ Arg-3.1 induction via binding to this proximal region (24).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our own data suggested that a proximal region possessed a 2-to 3-fold transcriptional activation ability, consistent with a previous study that showed the contribution of cAMP/MAPK pathways in the activity-dependent response mediated by this region (23). Furthermore, Egr-1/3 may also mediate the late, protein-synthesis dependent phase of Arc/ Arg-3.1 induction via binding to this proximal region (24).…”
Section: Discussionsupporting
confidence: 91%
“…Prior studies have demonstrated the role of a proximal region (Ͻ2 kb) of the Arc/Arg-3.1 promoter in its activity dependence (23,24). Consistent with this, proximal regions [Arc1000 (Ϫ996 to ϩ198) and Arc2000 (Ϫ1996 to ϩ198)] showed 2-to 3-fold induction after stimulation in our assays (Fig.…”
Section: Presence Of a Strong Synaptic Activity-responsive Element Insupporting
confidence: 90%
“…An exception to this pattern was that the expression of the IEGs Egr2 and Arc was regulated by burn injury for isolation reared rats, though in opposite directions. Egr genes do alter the expression of Arc (Li, Carter et al 2005) so it is possible that a signaling cascade specific to Egr2 and Arc is affected by burn injury healing during isolation rearing. Nonetheless, during burn injury healing, these genes, as with the other IEGs, were suppressed relative to both injured and uninjured group reared rats.…”
Section: The Immediate Early Gene Expression Changes Parallel the Behmentioning
confidence: 99%
“…A recent study in this Journal (Gallitano-Mendel, Izumi et al 2007) found that when the transcriptional IEG Egr3 is knocked out, mice show a hyperactive response in the open field. These authors suggest that the absence of this IEG, which transcribes the effector IEG Arc (Li, Carter et al 2005) and regulates long term potentiation (LTP) and long term depression (LTD) of neuronal synapses (Plath, Ohana et al 2006), results in open field hyperactivity due to decreased habituation to its novelty. Consistent with this, impaired expression of the IEG Arc is associated with deficient long term memory and increased exploration of a novel object (Plath, Ohana et al 2006).…”
Section: Link Between Between Behavioral and Ieg Changes During Isolamentioning
confidence: 99%
“…These genes have thus been used experimentally as markers of regional brain activity in response to a wide range of stimuli. In addition, these genes play important roles in synaptic plasticity, learning, and memory (Yamagata et al, 1994;Jones et al, 2001;Bozon et al, 2002Bozon et al, , 2003Li et al, 2005). However, much less is known about the involvement of these genes in the regulation of behavior, or in the organism's response to pharmacologic agents, or other stimuli that activate their expression in the brain.…”
Section: Introductionmentioning
confidence: 99%